The Purpose and Promise of Creation According to the Letter to the Romans: A Contribution to Christian Environmental Ethics - Christoph W. Stenschke (Journal of Dharma, 2025)
This article offers an exploration of how Paul’s references to creation in his Letter to the Romans can contribute to Christian environmental ethics. After an introduction to the debate and a survey of research, Romans 1:19–21; 8:19–22 and 11:26–27 is treated in detail. For each passage, the article discusses its implications for the environment and for human interaction with it. As creation testifies to its creator, humans need to do all to preserve it so that this testimony is also available to future generations. In its present suffering, creation is portrayed as participating in the human longing for the consummation of the Kingdom of God. As we wait together, humans are to treat creation as carefully as possibly as their co-heir of God’s promises and comprehensive salvific purposes. Built on this expectation and in view of Old Testament and early Jewish eschatology, there is the prospect not only of the salvation and restoration of all of Israel but also of all of creation. Read in this way, Romans can contribute to Christian ecological ethics.